Monocyte metabolism and function in patients undergoing cardiac surgery - Mayer, Daniel; Altvater, Marc; Schenz, Judith; Arif, Rawa; Karck, Matthias; Leuschner, Florian; Weigand, Markus A.; Uhle, Florian; Lichtenstern, Christoph (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveCardiopulmonary bypass (CPB) can lead to systemic inflammation, which is associated with higher morbidity. Therefore, we investigated the metabolism of isolated blood monocytes before and after CPB compared to healthy controls.MethodsIn this prospective, monocentric, observational study, we included 30 patients undergoing CPB and 20 controls. We isolated monocytes from heparinized blood and investigated their metabolism by using Seahorse technology before (t0), 4 h (t4), and 24 h (t24) after the start of the CPB. We also examined programmed cell death 1 ligand (PD-L1), PD-L2, V-domain Ig suppressor of T cell activation (VISTA), and human leukocyte antigen-DR isotype (HLA-DR) using fluorescence-activated cell sorting analysis. Additionally, we investigated plasma cytokine levels in patients without and after ex vivo stimulation.ResultsCPB-induced inflammatory responses are shown by significantly elevated plasma interleukin-6 levels in the CPB group compared to baseline and controls [t0: 0 ng/ml (95%CI 0-0 ng/ml); t4: 0.16 ng/ml (95%CI 0.1-0.197 ng/ml), p < 0.0001; t24: 0.11 ng/ml (95% CI 0.1-0.16 ng/ml), p < 0.0001, and controls: 0 ng/ml (95% CI 0-0 ng/ml)]. The cytokine release in the ex vivo stimulation is reduced for lipopolysaccharide stimulation at t4 [t0: 35.68 ng/ml (95% CI 22.17-46.57 ng/ml) vs. t4: 15.02 (95% CI 10.25-24.78 ng/ml), p < 0.0001]. Intracellular metabolism of monocytes after CPB showed a protracted shift to aerobic glycolysis [t0: 179.2 pmol/min (95% CI 138.0-205.1 pmol/min) vs. t24: 250.1 pmol/min (95% CI 94.8-300.2 pmol/min), p < 0.0001]. Additionally, we observed an altered metabolism in monocytes in patients undergoing cardiac surgery compared to controls even before any surgical procedure [t0: 179.2 pmol/min (95% CI 138.0-205.1) vs. controls 97.4 (95% CI 59.13-144.6 pmol/min), p = 0.0031].ConclusionAfter CPB, patients' monocytes show a shift in metabolism from oxidative phosphorylation to aerobic glycolysis, which is associated with energy-demanding and proinflammatory processes. This is the first study to show changes in monocyte immunometabolism in cardiac surgery. Monocytes of patients undergoing cardiac surgery were leaning toward aerobic glycolysis even before any surgical procedure was conducted. Leaving the question of the pathophysiological mechanisms for future studies to be investigated and paving the way for potential therapy approaches preventing inflammatory effects of CPB.